2011
DOI: 10.1111/j.1365-2265.2010.03963.x
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of subclinical hypercortisolism in patients with bilateral adrenal incidentalomas: a challenge to management

Abstract: Subclinical hypercortisolism is significantly more prevalent in bilateral incidentaloma patients, posing great dilemmas for its optimum management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
50
2
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 38 publications
7
50
2
4
Order By: Relevance
“…Previous observational data have shown a consistent relationship between the size of the adenoma and the degree of autonomous cortisol secretion [8]. More recently we reported that bilateral incidentalomas exhibit SH more frequently than their unilateral counterparts [4]. The authors confirm these findings but the novelty of this study is that the probability of SH also relates inversely to the unenhanced CT attenuation values of the adrenal lesions.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Previous observational data have shown a consistent relationship between the size of the adenoma and the degree of autonomous cortisol secretion [8]. More recently we reported that bilateral incidentalomas exhibit SH more frequently than their unilateral counterparts [4]. The authors confirm these findings but the novelty of this study is that the probability of SH also relates inversely to the unenhanced CT attenuation values of the adrenal lesions.…”
supporting
confidence: 79%
“…A significant proportion of patients, about 15 %, have bilateral lesions [4]. Since most adrenal incidentalomas arise from adrenal tissue, a substantial proportion of them are functional in terms of autonomous production of various adrenal hormones, including cortisol, aldosterone, catecholamines or rarely androgens.…”
mentioning
confidence: 99%
“…This finding persisted when patients with UAI were analyzed separately from patients with BAI, as described previously (17,18). In another study, the size of adrenal mass was positively related to hormonal abnormalities compatible with subtle cortisol hypersecretion (namely, positively related to serum post-LDDST cortisol levels and negatively related to ACTH and DHEA-S levels) in the whole cohort (15). We also found that the probability of SCS in the whole cohort of patients correlates positively with the adrenal mass size, in agreement with previous data (17).…”
Section: European Journal Of Endocrinologymentioning
confidence: 59%
“…Although the etiology and pathogenesis of sporadic adrenal tumors are under research, there are few data suggesting possible pathogenetic differences between unilateral adrenal incidentalomas (UAI) and BAI (13,14). Recently, the possibility of a different prevalence in SCS and in clinical characteristics between patients with UAI and BAI has been examined; however, existing data are limited and controversial (15,16,17,18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation